Pengaruh Bahan Pengisi Terhadap Massa Cetak Tablet Vitamin C - Nawangsari, Desy (Viva Medika, 2019)
Avicel® PH is branded name from microcrystalline cellulose that is generally used in pharmaceutical preparations. Avicel® PH are being used as filler or binder in dosage formulas in tablets especially for direct compression because having a good flowing rate and a good compressibility. This study aims to compare the influence of the use Avicel® PH 101 and Avicel® PH 102 as a filler on of preparations a tablet of ascorbic acid. A method of the research was conducted by making granule of ascorbic acid tablet with the variation filler, then the granule was evaluate in .The results showed Avicel® PH 102 as a filler produce granule which better seen from the flowability, static angle of repose, carr’s index and hausner ratio .